Accountability of the Minahasa Regency Regional General Election Administration (KPUD) (Study on the 2018 Minahasa Regency Head Election) - Agnesia Benedictta C. Tewu (Syntax Corporation Indonesia, 2021)
This study aims to analyze the accountability of the general election administration in the Minahasa Regency. This research uses qualitative methods, direct research to data sources and researchers are the key instruments. Qualitative research emphasizes the process of searching for the meaning behind the phenomena that arise in research with the aim that the problems studied are more in-depth, natural, and as they are without interference from researchers. From the results of the study, it was found that accountability is an ethical concept that is close to government public administration (government executive institutions, parliamentary legislative institutions, and judicial institutions) this is often used synonymously with concepts such as accountability, the ability to provide answers (answerability) that can be blamed (blameworthiness) and which have liability, including other terms that have no connection with the hope of being able to explain part of one aspect of public administration. The technical guidance received by PPS and KPPS is just a matter of election procedures. Submission of other information to voters is still carried out directly by the KPU and its implementation is not too optimal and not yet accountable, where the limitations of KPU members are not good in quantity. Then for suggestions to make it even better, it is recommended that the implementation of the Regional Election for the Regional Head Election of the Minahasa Regency KPUD should be more accountable from the preparation stage to the announcement stage of the Pilkada winner.